2006
DOI: 10.1002/ajh.20652
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of low-molecular-weight heparin-induced bleeding in patients with pre-existing hypercoagulable states with human recombinant activated factor VII concentrate

Abstract: Low-molecular-weight heparins are widely employed in prophylactic and therapeutic antithrombotic regimens for venous thromboembolic events. Excessive anticoagulation with lowmolecular-weight heparins rarely can precipitate catastrophic bleeding complications. Currently, there is no specific or reliable antidote that can reverse the anticoagulant effects of low-molecular-weight heparins efficiently and safely. This report describes three individuals with underlying hypercoagulable states, who developed clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…There is however the possibility that such bleeds may be aggravated by LMWH treatment, but one study found no difference in the mean number of blood products administered to cirrhotic patients with LMWH-associated bleeding compared with bleeds from other causes suggesting that thromboprophylaxis with LMWH has limited adverse effects on bleeding gravity in this context [37]. This notion is further substantiated by the fact that recombinant factor VIIa, one of the most powerful procoagulants and a known reverser of LMWHassociated bleeding [113], has proven ineffective at controlling variceal bleeding in cirrhotic patients in randomized controlled trials [114,115]. In other words, a coagulation deformation may not be a predominant factor influencing the severity of variceal bleeding and implies that any intervention in the coagulation system, including anticoagulation with LMWH, will likely have a limited effect in determining their gravity.…”
Section: Safety Of Antithrombotic Therapymentioning
confidence: 99%
“…There is however the possibility that such bleeds may be aggravated by LMWH treatment, but one study found no difference in the mean number of blood products administered to cirrhotic patients with LMWH-associated bleeding compared with bleeds from other causes suggesting that thromboprophylaxis with LMWH has limited adverse effects on bleeding gravity in this context [37]. This notion is further substantiated by the fact that recombinant factor VIIa, one of the most powerful procoagulants and a known reverser of LMWHassociated bleeding [113], has proven ineffective at controlling variceal bleeding in cirrhotic patients in randomized controlled trials [114,115]. In other words, a coagulation deformation may not be a predominant factor influencing the severity of variceal bleeding and implies that any intervention in the coagulation system, including anticoagulation with LMWH, will likely have a limited effect in determining their gravity.…”
Section: Safety Of Antithrombotic Therapymentioning
confidence: 99%
“…If bleeding occurs, protamine sulfate may provide partial neutralization. 31 There are reports of the successful use of recombinant activated factor VII concentrate to reverse LMWH-induced bleeding in nonpregnant patients with underlying hypercoagulable states; 32 however, experience with this strategy is limited, and there continue to be concerns about the thrombogenicity of recombinant factor VIIa. Therefore, this intervention should be reserved for major bleeding unresponsive to conventional therapy.…”
Section: Management Of Anticoagulant Therapy At the Time Of Deliverymentioning
confidence: 99%
“…Guidelines and several case reports have suggested different reversal strategies including empirical FFP, PCC, aPCC, and rFVIIa [6]. However, no wellpowered clinical studies have been performed to determine the effectiveness of these strategies to reverse the anticoagulant effects of LMWHs.…”
Section: Discussionmentioning
confidence: 99%